A estrutura institucional do APL de confecções do agreste pernambucano e seus reflexos sobre a cooperação e inovação: o caso do município de Toritama - Andrade, Tabira de Souza (2008)
This work search to investigate the institutional structure of the Productive Arrangement of Makings of Pernambuco, emphasizing the case of the municipal district of Toritama, integral important of the branch of makings in the area of the rural of that state, whose main activity is the production of pieces jeans. Basing on the focus neo-schumpeteriano/ evolutionist and in the theory institutional, used in the construction of the theoretical approach of productive arrangements and local inovativos, it intends to demonstrate that the intense growth presented by Toritama, will only have long course if there are the presence of technological capacities and endogenous innovative which are strengthened and developed starting from the relationships of local cooperation and of the incentive of an appropriate and dynamic institutional atmosphere. For so much, the adopted methodology consists of the accomplishment of an empiric research in located companies in the municipal district and in support institutions and fomentation placed in Toritama and in other places of the arrangement, specifically, Santa Cruz do Capibaribe, Caruaru and Recife, capital of the state of Pernambuco. The results point that the cooperative practices are still incipient so much among the companies, as among the institutions, as well as of these last ones with the own companies. And that efforts exist on the part of some productive and institutional actors in the search and introduction of innovations, in way the if they maintain at the market of the fashion, which is characterized by being quite competitive and extremely prone to fast changes. Recently, new institutional entities were created in face to the expansion of the activity and of the need to supply certain existent lacks, above all, of qualification and training of the labor, whose reflexes will only be able to be felt in the long period.